The obstacles to developing a curricular perspective sensitive to differences and possibilities of change in the practice - García Pastor, Carmen (Profesorado, Revista de Currículum y Formación del Profesorado, 2012)
We assume in this work that, meeting with diversity in education is a question of justice curriculum. On the one hand, we point out the obstacles that prevent from advancing to a curriculum which is more equitable, more responsive to the recognition of differences. On the other hand, we revise some questions that should be taken into account in practice, if we think that teachers have to meet not only with common needs of students but also with the particular ones, because that is precisely what a policy of recognition of differences means. Lastly, we point out some important elements to change practice that stem from specialized literature and from our own work developed with teachers.